NAUNGAN DALAM PERSPEKTIF AL-QUR'AN : STUDI TAFSIR MAUDHU'I - marito hasibuan (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This research is motivated by the diversity of meanings of shade (zhilȃl). The word shade (zhilȃl) has been understood as positive, such as shade, shadows, shade and so on. However, the author found shade (zhilȃl) which has negative meanings, as found in the word of God surah al-Wȃqi'ah verse 43